2018
DOI: 10.1021/acs.energyfuels.7b03484
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurements of Chemiluminescence in a Laminar Methane–Air Premixed Flame and Comparison to Numerical Methods

Abstract: Quantitative measurements of chemiluminescence emissions as a result of CH*, OH*, C 2 *, and CO 2 * were conducted in CH 4 /air premixed flames at different equivalence ratios (θ = 0.7−1.33), and numerical results based on onedimensional flame simulations were compared to these data. A wavelength-dependent and optical-path-corrected emission calibration method was applied to quantify the emission of each excited species. The numerically simulated emission intensities of OH* and CH* are within the same order of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…However, they failed to take into account the effects of nonradiative transitions of OH*. It is noteworthy that Wang et al 35 introduced a Monte Carlo tracing of photons to correct the optical paths of a CH 4 /air plane premixed flame, and the wavelength responsivity of the optical detection system was calibrated using a quartz tungsten halogen lamp. They found that the concentration distributions of CH*, OH*, C 2 *, and CO 2 * are consistent with simulation results, but this method only works for one-dimensional plane flames.…”
Section: Introductionmentioning
confidence: 99%
“…However, they failed to take into account the effects of nonradiative transitions of OH*. It is noteworthy that Wang et al 35 introduced a Monte Carlo tracing of photons to correct the optical paths of a CH 4 /air plane premixed flame, and the wavelength responsivity of the optical detection system was calibrated using a quartz tungsten halogen lamp. They found that the concentration distributions of CH*, OH*, C 2 *, and CO 2 * are consistent with simulation results, but this method only works for one-dimensional plane flames.…”
Section: Introductionmentioning
confidence: 99%
“…Further work has examined and sought to optimize the prediction of flame location [32]. Full coupling of sub-mechanisms for CH* were previously shown to have negligible effects on the flame characteristics due to its orders of magnitude difference in concentration [33,34]…”
Section: Simulationsmentioning
confidence: 99%